PENGARUH DISKON DAN TAGLINE “GRATIS ONGKOS KIRIM” TERHADAP KEPUTUSAN PEMBELIAN DI E-COMMERCE SHOPEE (Studi Kasus Pada Masyarakat Kota Semarang) - Aeni, Alfi Nur; Hendrayanti, Silvia (E-Prosiding Seminar Nasional Manajemen dan Akuntansi STIE Semarang (SNMAS), 2024)
This research aims to determine the influence of discounts and the tagline "free shipping" on purchasing decisions at Shopee (study of the people of Semarang city). The population of this research is all residents of the city of Semarang who use the Shopee application. The sample used in this research was 97 respondents. This research uses a quantitative method with purposive sampling. Data was collected using an online questionnaire distributed via a Google Form link to respondents. Data analysis uses SPSS 28 which includes validity, reliability, classical assumption tests, multiple linear regression analysis, hypothesis testing using the t test, f test and R2 test. The results of this research show that the discount variable has a positive effect with t count (3.299) > (1.665) t table and sig value. 0.001< sig.α (0.05), the tagline "free shipping" has a positive and significant effect with the calculated t value (6.091) > (1.665) t table and the sig value. <0.001 < sig.α (0.05). For further research, it would be better to add different variables such as payment by Spaylater, COD (Cash On Delivery), Consumer Reviews and develop research on factors that can influence purchasing decision variables.